Man of the year - Walker, Caroline Louise (Gallery Books, 2019)
Dr. Robert Hart, Sag Harbor<U+2019>s just-named Man of the Year, is the envy of his friends and neighbors. His medical practice is thriving. He has a beautiful old house and a beautiful new wife and a beautiful boat docked in the village marina. Even his wayward son, Jonah, is back on track, doing well at school, finally worthy of his father<U+2019>s attentions. So when Jonah<U+2019>s troubled college roommate, Nick, needs a place to stay for the summer, Hart and his wife generously offer him their guest house. A win-win: Jonah will have someone to hang with, and his father can bask in the warm glow of his own generosity. But when he begins to notice his new houseguest getting a little too close to his wife, the good doctor<U+2019>s veneer begins to crack. All the little lies Robert tells<U+2014>harmless falsehoods meant to protect everything he holds dear<U+2014>begin to mount. Before long, he<U+2019>s embroiled in a desperate downward spiral, destroying the lives that stand in his way. It<U+2019>s only the women in his life<U+2014>his devoted office manager, his friends, his wife<U+2014>who can clearly see the truth.